The wellbeing pandemic: Outline of a contested terrain and a proposed research agenda - Jackson, Steven J.; Sam, Michael P.; Dawson, Marcelle C.; Porter, Daniel (Frontiers in Sociology, 2022)
Wellbeing has emerged as a central, if not defining, feature of contemporary social life. Yet, despite its global significance spanning the political, social and economic spectrum, there is a remarkable lack of agreement regarding the conceptualisation, definition or operationalisation of wellbeing nor any clear evidence of its success as an instrument of policy. This essay explores the contested terrain of wellbeing by examining the concept in relation to emerging politics, complexities and contradictions. More specifically, the essay: (1) briefly describes the historical origins and development of wellbeing; (2) discusses how it has been reconceptualised within the context of neoliberalism; and, (3) outlines a research agenda offering three ways to investigate wellbeing including: (a) as a wicked problem; (b) as part of the process of ‘wellbeing washing’ within state and other institutional structures and policies; and, (c) in relation to alternative futures, which might encourage us to reimagine or jettison the term altogether.